2016
DOI: 10.16965/ijims.2016.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella Sativa seed and Thymoquinone on Reproductive Parameters in Sterptozotocine Induced Diabetic and Normal Male Albino Rats

Abstract: Introduction:In diabetes an increase in free radicals, DNA damage and lipid peroxidation in human sperm may occur. Antioxidant components in medicinal herbs such as Nigella sativa have been indicated to improve spermatogenesis and steroidogenesis. Thymoquinone and unsaturated fatty acids are the main antioxidant components of Nigella Sativa. Nigella Sativa seeds has been used in traditional Iranian medicine as a natural remedy for promotes females menstruation, galactagogue, carminative, laxative and anti-para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…These are also consistent with a previous study that TQ had significantly improved the plasma testosterone level and epididymal sperm count caused by administration of lead [32]. In addition, several reports have shown that TQ plays a role to increase Leydig cell number and testosterone levels which eventually improved spermatogenesis [33,34]. Thymoquinone also exerts marked antioxidant characteristic which could ameliorate the spermatogenesis impairment caused by testicular injury through oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…These are also consistent with a previous study that TQ had significantly improved the plasma testosterone level and epididymal sperm count caused by administration of lead [32]. In addition, several reports have shown that TQ plays a role to increase Leydig cell number and testosterone levels which eventually improved spermatogenesis [33,34]. Thymoquinone also exerts marked antioxidant characteristic which could ameliorate the spermatogenesis impairment caused by testicular injury through oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…TQ significantly attenuated cadmium-and lead-induced decreases in serum testosterone in rats (Fouad, Albuali, & Jresat, 2014) and (Mabrouk & Ben Cheikh, 2016).TQ ameliorated testicular tissue inflammation and restored the normal balance of sex hormones; testosterone, LH and FSH induced by sodium nitrite both in vivo and in vitro (Alyoussef & Al-Gayyar, 2016). Aithal et al(Aithal, Haseena, Das, & Saheb, 2016) also showed that TQ increased the serum testosterone levels in arsenic-induced and sterptozotocine-induced testicular toxicity in male rats. Capsaicin significantly increased the serum levels of testosterone, FSH and LH.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, TQ administration significantly increased serum testosterone level and AR expression in the testis. This may be attributed to the preservation of Leydig cells through its antioxidant effect or its ability to enhance aromatase gene expression, which subsequently enhanced spermatogenesis ( Aithal et al, 2016 ; Negi et al, 2018 ). In the same line of these findings, TQ has been described to have fertility-enhancing effect ( Wani et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%